Nonaromatic Amine Containing Exciplex for Thermally Activated Delayed Fluorescent Electroluminescence. Issue 9 (18th February 2019) - Cai, Xinyi; Qiu, Weidong; Li, Mengke; Li, Binbin; Wang, Zhiheng; Wu, Xiao; Chen, Dongcheng; Jiang, Xiaofang; Cao, Yong; Su, Shi‐Jian
Abstract: A novel nonaromatic amine containing hole‐transporting material, 3, 3′‐(2‐methyl‐1, 3‐phenylene)diphenoxathiine (mPXTMP), is developed and coevaporated with electron‐transporting materials to form comixed films. Pure‐blue, sky‐blue, and green thermally activated delayed fluorescent (TADF) exciplex emissions are observed. Though the mPXTMP:2, 4, 6‐tri([1, 1′‐biphenyl]‐3‐yl)‐1, 3, 5‐triazine (T2T) bimolecular system exhibits a large singlet–triplet splitting energy (Δ E ST ) of 0.44 eV, its locally triplet excited states play vital roles in the cascade up‐conversion process, leading to an abnormal synergistic enhancement of TADF and phosphorescence from high‐lying triplet states at a low temperature, which violates Kasha's rule. Another bimolecular system, mPXTMP:PO‐T2T, achieves a fast up‐conversion rate of 10 6 s −1 benefiting from a small Δ E ST of 0.10 eV and the enhanced spin–orbital coupling induced by the sulfur element rich environment. The corresponding organic light‐emitting diodes realize an exciton utilization ratio of 61.7–92.6%, verifying that these nonaromatic amine containing exciplex systems can be promising candidates toward purely organic electroluminescence with 100% internal quantum efficiency. Abstract : Pure‐blue and green nonaromatic amine containing exciplex thermally activated delayed fluorescent electroluminescence is realized. The nonaromatic amine containing exciplex system containing a sulfur element promotes spin‐orbital coupling (SOC), leading to a fast reverse intersystem crossing process. A corresponding green device achieves an exciton utilization ratio of 61.7–92.6%, far exceeding the theoretical limits of 25% for traditional fluorescent organic light‐emitting diodes.